Electrochemical control meets enhanced Raman sensitivity: a critical review of electrochemical surface-enhanced Raman spectroscopy (EC-SERS) sensors - Katia Buonasera; Maurilio Galletta; Gianni Pezzotti Escobar; Simone Failla; Maria José Lo Faro; Francesco Priolo; Giovanna De Luca; Barbara Fazio; Antonio Alessio Leonardi; Alessia Irrera (Analytica Chimica Acta, 2026)

Coral health status before and after the tourism halt caused by the COVID-19 pandemic in Koh Tao (Thailand) - Matilde Baruffaldi; Camilla Roveta; Elouise S. Haskin; Simone Fazio; Chad Scott; Kirsty Magson; Cristina Gioia Di Camillo (Coral Reefs, 2026)

Correction: Elementary flow mapping across life cycle inventory data systems: A case study for data interoperability under the global life cycle assessment data access (GLAD) initiative - Antonio Valente; Carl Vadenbo; Simone Fazio; Koichi Shobatake; Ashley Edelen; Thomas Sonderegger; Selim Karkour; Oliver Kusche; Edward Diaconu; Wesley W. Ingwersen (The International Journal of Life Cycle Assessment, 2025)

Elementary flow mapping across life cycle inventory data systems: A case study for data interoperability under the Global Life Cycle Assessment Data Access (GLAD) initiative - Antonio Valente; Carl Vadenbo; Simone Fazio; Koichi Shobatake; Ashley Edelen; Thomas Sonderegger; Selim Karkour; Oliver Kusche; Edward Diaconu; Wesley W. Ingwersen (The International Journal of Life Cycle Assessment, 2024)
Purpose Limited availability of life cycle assessment (LCA) data poses a significant challenge to its mainstream adoption, rendering it a central issue within the LCA community. The Global LCA Data Access (GLAD) network aims to increase the accessibility and interoperability of LCA data and offers benefits for different use cases. GLAD is an intergovernmental collaboration involving different stakeholders organized into working groups. The GLAD Nomenclature Working Group (NWG) developed a procedure and a set of criteria to map elementary flows among major nomenclature systems and reviewed bidirectional mappings. This paper provides an overview of the methodological approach followed by the NWG to achieve the resulting mapping files. Methods The mapping procedure involves several steps of flow and compartment matches and bilateral review. The procedure is supported by an ad hoc software tool called the “GLAD Mapper Tool” developed with the NWG and which is made available for free by the European Commission. The input files for the procedure are the properly formatted source and target flow lists and a file containing the mapping criteria. The four nomenclature systems mapped are those used in ecoinvent, Environmental Footprint, IDEA, and the U.S. Federal LCA Commons. The procedure included representatives from each of these nomenclature systems to ensure a multilateral agreement on the approach to verifying and assessing the quality of the results. The iterative mapping process included different stages of bidirectional reviews to achieve a balance between mapping coverage (i.e., percentage of source flows covered by the target list) and accuracy. Results and discussion The mapping procedure proved to be an efficient approach for LCA practitioners in mappings between different nomenclature systems. After a relatively low number of iterations, mapping coverages higher than 90% were achieved, which is driven by the availability of unique substances (flow names) and the granularity of environmental compartments. Overall, none of the four flow lists achieved full coverage and the use of approximated matches (proxy matches) for environmental compartments and/or substances was necessary when a perfect matches between flows were not possible. Conclusions The NWG’s mapping activities may serve as a starting point towards defining a central hub for mapping impact assessment methods and datasets, improving data accessibility and interoperability for the LCA community as a step towards defining a unified nomenclature system. The GLAD mapping approach is open and transparent. The approach fosters traceability in the mapping process and offers the potential for greater interoperability across the LCA community, underlining the commitment to openness and collaboration.

Linking inventories and impact assessment models for addressing biodiversity impacts: mapping rules and challenges - Esther Sanyé-Mengual; Antonio Valente; Fabrizio Biganzoli; Martin Dorber; Francesca Verones; Alexandra Marques; Jorge Ortigosa Rodriguez; Valeria De Laurentiis; Simone Fazio; Serenella Sala (The International Journal of Life Cycle Assessment, 2022)
Purpose An adequate matching between the nomenclature of elementary flows in life cycle inventory (LCI) databases and life cycle impact assessment (LCIA) methods is key for ensuring the proper application of life cycle assessment (LCA). However, the nomenclature of elementary flows lacks harmonization among the LCA community. This paper aims at defining mapping rules and discussing main challenges related to the process of systematically mapping LCI nomenclatures to LCIA methods and models addressing biodiversity impacts. Methods Eight LCIA methods and models addressing biodiversity loss are analyzed: five comprehensive LCIA methods (i.e., LC-IMPACT, Impact World + , Ecological Scarcity 2013, ReCiPe 2016, and Stepwise), one land use intensity-specific LCIA model; and two approaches adapting the GLOBIO model to LCIA. These models and methods are mapped to two LCI nomenclatures (ecoinvent v3.6 as implemented in Simapro and Environmental Footprint (EF) 3.0). A mapping tool was developed to support the process of (a) mapping elementary flows by name, Chemical Abstract Service number or available synonyms; (b) implementing specific mapping rules regarding compartment/sub-compartment, and substance name; (c) mapping elementary flows to manually defined proxies (e.g., synonyms, spelling corrections and similar substances); and (d) assigning characterization factors (CFs). The process entails analyzing a case study to identify uncharacterized elementary flows. Results and discussion We present a mapping of LCIA methods and models addressing impacts on biodiversity loss with specific LCI nomenclatures. Mapping rules are proposed for elementary flows regarding chemicals, carbon emissions, land use, water use, and particulate matter. Specific aspects to be considered in mapping elementary flows in LCIA and LCI nomenclatures are discussed. Main gaps in LCI nomenclatures are associated to toxicity and climate change impacts. The EF 3.0 was more aligned than ecoinvent 3.6 with the LCIA methods and models regarding elementary flows coverage and regionalization level. Analyzing uncharacterized flows revealed further coverage needs for “Chemical, organic” (between 19 and 20% uncharacterized flows), “Chemical, inorganic” (between 9 and 18% uncharacterized flows) and “Chemical, radioactive” (between 9 and 14% uncharacterized flows). Conclusions This paper contributes to the operationalization of LCIA methods and models addressing biodiversity impacts by proposing a systematic mapping process and rules for a better LCIA-LCI connection. Different development pathways of LCI (e.g., focused on substance name detail) and LCIA (e.g., towards improved regionalization level) have stretched the gap between both nomenclatures. Recommendations are provided identifying further efforts towards the harmonization of the nomenclature of elementary flows in the LCA community.

Challenges and opportunities for web-shared publication of quality-assured life cycle data: the contributions of the Life Cycle Data Network - Marco Recchioni; Gian Andrea Blengini; Simone Fazio; Fabrice Mathieux; David Pennington (The International Journal of Life Cycle Assessment, 2015)

The presence of clustered circulating tumor cells (CTCs) and circulating cytokines define an aggressive phenotype in metastatic colorectal cancer - Rosa Divella; Antonella Daniele; Ines Abbate; Antonia Bellizzi; Eufemia Savino; Giovanni Simone; Grazia Giannone; Francesco Giuliani; Vito Fazio; Gennaro Gadaleta-Caldarola; Cosimo Damiano Gadaleta; Ivan Lolli; et al. (Cancer Causes & Control, 2014)